Determinant of BPJS Ketenagakerjaan Payment Premiums (Case Study of Employment BPJS Branch Offices in Tangerang City): BPJS, IPB University (Jurnal Ekonomi dan Kebijakan Pembangunan, 2023)
The smooth payment of BPJS Ketenagakerjaan premiums is very dependent on the obligatory contributions of participants, namely the compliance of companies/employers in paying contributions every month. Having healthy finances can improve services and business processes at Employment BPJS which can be seen from the addition of membership, increased receipt of contributions and reduced contribution arrears. Studies on the factors that influence the smooth payment of contributions at Employment BPJS are still very rarely researched, so it is necessary to conduct research for this purpose, especially when the Covid-19 pandemic hit and carry out further research on the performance of branch offices. The research was conducted at the Tangerang Batuceper BPJS Ketenagakerjaan branch office of 3,564 assisted companies using 2021 data. Using the logit method, the economic variables studied were company demographics, socio-economics, safety issues, ease of service and government and policy enforcement. The results obtained are that the number of workers, the risk of work accident security scale, company assets and turnover, the amount of contributions, and the convenience of services such as SIPP Online and JMO Mobile, as well as the number of claims for old age security balances are variable factors that significantly affect the smoothness of payment of contribution premiums. Therefore, in order to reduce arrears in contributions, Employment BPJS must increase payment channels, provide information through the media, collect arrears of contributions via SMS and telephone or cooperate with the local government in terms of law enforcement and joint direct visit.